If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + 3 + 2x = -11 Reorder the terms: 3 + -9x + 2x = -11 Combine like terms: -9x + 2x = -7x 3 + -7x = -11 Solving 3 + -7x = -11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + -7x = -11 + -3 Combine like terms: 3 + -3 = 0 0 + -7x = -11 + -3 -7x = -11 + -3 Combine like terms: -11 + -3 = -14 -7x = -14 Divide each side by '-7'. x = 2 Simplifying x = 2
| 15y+-10+1=2(ky+-1)+-1y | | 15y+-10+3=2(ky+-1)+-1y | | 3y+3x=45 | | 2r-5s=k | | -4x+5-2x+3= | | 15y+-10+6=2(ky+-1)+-1y | | X^2-11x=-56 | | (0)=-4.8x+1.2 | | (2.5b-9)+6b=-7 | | 8m-6=2 | | 5(a-1)=5 | | 5(3x+-2)=4+-6x | | 4(3x+-2)=4+-6x | | -11=7+b | | 4w+10=90 | | 43v-6=8+23v | | 12x+6=5y+10 | | 4w+10= | | 2x-3(3-7)+3= | | 3(3x+-2)=4+-6x | | Y=-4.8(0)+1.2 | | 2(3x+-2)=4+-6x | | 150m-125m+38200=40400-175m | | 6m-2=m+3 | | (54b-27ab)= | | 2x^2-20=8 | | 3n+8=92 | | 20y=25y^2 | | 5x-11=8x+12 | | 4x-20.65=6.7 | | 3x+y=7xy | | 0.5x+0.1*5x=62.15 |